Risks, Problems and Profitability of Seed Production in Puducherry - A. POUCHEPPARADJOU; K. THIMMAPPA; G. SARADA; K. VIJAYASARATHY (Seed Research, 2026)
An attempt was made to study the risks, problems and profitability of seed production in the Union Territory of Puducherry. Primary data on the risk involved, problems faced by the seed growers and cost of cultivation of both seed and commercial crops were collected from the representative farmers. The conventional tabular and percentage analyses were used to analyze the data. The findings indicate that seed production is profitable but risky. The farmers withdrew from the seed production programme in the initial stage due to non-availability of seeds, poor rainfall, poor germination, grazing and admixture. During the final stages of seed production, farmers faced the risk of rejection due to presence of other distinguishable varieties and germination failures. The farmers also faced problems of late payment made by the purchasing agency, late release of subsidy, timely non-availability of seeds and delay in processing. The analysis on economics of seed production showed that the expenditure on seed production specific activities like, drying, marketing, registration and field inspection contributed towards the differences between the seed and commercial production. The findings of the study indicate that the cost of cultivation was higher in seed production as compared to the commercial crop production. But the total return was higher in seed production than commercial crop production.